2010
DOI: 10.1080/10502550903455174
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Family Factors Related to Psychosocial Adjustment in Stepmother Families With Adolescents

Abstract: This article presents additional data analyses from an earlier study on risk and resilience factors linked with adjustment in stepfamilies with adolescents. The primary objective addressed how individual and family-level factors impacted adjustment in a sample composed of 3 members (biological father, stepmother, and adolescent) from a subsample of 39 stepmother families. Multiple regression results showed that each stepmother family member's adjustment is affected by both shared and nonshared processes.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Previous research has identified that a number of family and individual factors can contribute to stress among stepparents, including a lack of boundaries and role clarity (Gosselin, ; Sweeney, ), both familial and societal expectations (Fine & Schwebel, ; Nielsen, ), and tense relationships with other family members (Shapiro & Stewart, ). However, the current literature is lacking a systemic understanding of the ways in which social identities and roles, as well as associated cultural and individual expectations, interact with interpersonal processes to shape stepparents' experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified that a number of family and individual factors can contribute to stress among stepparents, including a lack of boundaries and role clarity (Gosselin, ; Sweeney, ), both familial and societal expectations (Fine & Schwebel, ; Nielsen, ), and tense relationships with other family members (Shapiro & Stewart, ). However, the current literature is lacking a systemic understanding of the ways in which social identities and roles, as well as associated cultural and individual expectations, interact with interpersonal processes to shape stepparents' experiences.…”
Section: Introductionmentioning
confidence: 99%
“…가족 레질 리언스는 문제해결과 성장을 위한 가족들의 잠재력을 확신하 며, 역경에 처한 가족을 문제가 많은 것으로 인식하기보다는 삶의 도전을 받고 있는 가족으로 여겨 그 관점의 전환을 가져 온다 (Walsh, 1998) (Gosselin & David, 2007;Gosselin, 2010;Walsh, 1998).…”
Section: 다수의 재혼가족은 많은 어려움 속에서도 원활한 의사소 통 및 상호협력을 통하여 문제를 해결할 수 있는 강점을 가지unclassified
“…That is, even without introducing a new partner into the family system, the lack of clarity about the parents' relationship status may disrupt the family system's functioning, including who counts as an insider or an outsider to the immediate family unit and who is responsible for which activities of daily living. These challenges could translate into impaired socioemotional and behavioral outcomes among adolescents via their impact on dyadic relationships in the family and disruptions in parental supervision (Gosselin, ).…”
Section: Introductionmentioning
confidence: 99%